Enhancement in thermoelectric properties of ZrNiSn-based alloys by Ta doping and Hf substitution. (July 2022) - Yang, Xiong; Wang, Yanxia; Min, Ruonan; Chen, Zongning; Guo, Enyu; Kang, Huijun; Li, Linwei; Jiang, Xue; Wang, Tongmin
Abstract: Though half-Heusler alloys are listed among the mid-high temperature thermoelectric materials with excellent thermoelectric and mechanical properties, their thermal conductivities remain high and limit their practical applications. In this work, the thermal conductivities and electrical conductivities of ZrNiSn-based alloys were synergistically optimized by Ta doping and Hf substitution. The samples were fabricated using levitation melting combined with spark plasma sintering. When compared with the pristine ZrNiSn, the electrical conductivity in Zr0.68 Hf0.3 Ta0.02 NiSn increases from 7.3 × 10 4 to 12.9 × 10 4 S·m −1, and the lattice thermal conductivity declines from 4.1 to 2.7 W·m −1 ·K −1 at 923 K. As a result, an enhanced ZT of 0.94 for Zr0.68 Hf0.3 Ta0.02 NiSn is achieved, which is a nearly 56% enhancement over pristine ZrNiSn. Furthermore, the microhardness, Young's modulus, and shear modulus in Zr1 -x-y Hf x Ta y NiSn ( x  = 0, 0.2, 0.3, 0.4; y  = 0, 0.02) alloys are substantially improved upon increasing the Ta and/or Hf content, far exceeding those in other conventional thermoelectric materials. Graphical abstract: High-quality Zr1 -x-y Hf x Ta y NiSn samples were prepared by levitation melting combined with spark plasma sintering. A ZT value of 0.94 was obtained at 923 K. The ZTavg values indicate that the Ta doping and Hf substitution of ZrNiSn-based alloys have attractive engineering potential, which is similar to that of Sb doping and Hf substitution. Zr1 -x-y Hf x Ta y NiSn with Hf doping of only 0.3 approaches the ZT value close to that of Sb-Hf co-doping (∼1.0). Moreover, the Zr1 -x-y Hf x Ta y NiSn alloys offer excellent mechanical properties, endowing them with a greater potential for industrial application. Image, graphical abstract